Analisis Kelayakan Finansial Usaha Ternak Itik Petelur Wijaya Farm di Nagari Jawi-Jawi Kecamatan Gunung Talang Kabupaten Solok Berdasarkan Perspektif Islam - Tisa Livia Zilka; Faisal Hidayat (ARZUSIN, 2026)
Layer duck farming businesses have received attention in several studies, but research that specifically discusses financial feasibility analysis integrated with the perspective of Islamic Economics remains limited. This study aims to analyze the financial feasibility of the Wijaya Farm layer duck business and to evaluate its conformity with the principles of Islamic Economics. This study employed a qualitative approach with a case study design, involving the business owner and workers selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using thematic analysis as well as financial feasibility calculations covering cash flow, payback period, average rate of return, net present value, profitability index, and break-even point. The results showed that the Wijaya Farm layer duck business was financially feasible, with a positive net cash flow of Rp1,240,858,000, a payback period of 4 years and 6 months, an average rate of return of Rp108,023,830, a net present value of Rp464,402,770, a profitability index of 16.48 times, and a break-even point that could be achieved and tended to decline from year to year. In addition, this business was also in accordance with the principles of Islamic Economics because it used personal capital without interest-based loans, thereby avoiding elements of riba, gharar, and maysir, and producing halal products. These findings contribute to the development of studies on investment feasibility and Islamic Economics and broaden understanding of livestock businesses based on sharia values. The conclusion of this study affirms the importance of financial feasibility analysis and sharia compliance in the development of livestock businesses, while also implying the need for more structured financial management for business actors.